Applied linguistics and materials development - Tomlinson, Brian, 1943- (Bloomsbury Academic, 2013)
Focuses for the first time on materials development and applications of current research and theory for the main areas of applied linguistics (e.g. second language acquisition, pragmatics, vocabulary studies). There are many books on applied linguistic theory and research and there are now a number of books on the principled development of materials for language learning, but this book takes a new approach by connecting the two concerns. Each of its chapters first of all presents relevant theories and research conclusions for its area and then considers practical applications for materials dev.